Efektivitas Implementasi Perlindungan Hukum Konsumen dalam Transaksi Digital pada Marketplace di Indonesia - Ananda Clarissa; Ika Dwi Maya Roza; Ashira Naila Susanti; Devi Riani; Muthia Salsabila (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The rapid growth of digital transactions through marketplace platforms has driven significant changes in the consumption patterns of Indonesian society. Behind the convenience and efficiency offered, online transactions also pose various legal risks for consumers, including product mismatches, fraudulent practices, and weak personal data protection. This situation creates an urgency to assess the effectiveness of the implementation of consumer legal protection in digital transactions. This study aims to analyze the level of effectiveness of consumer legal protection in digital transactions in Indonesian marketplaces and to identify obstacles in its implementation. The method used is normative legal research with an approach based on legislation and literature studies, particularly on the Consumer Protection Law, the Electronic Information and Transactions Law, and Government Regulation Number 80 of 2019. The research results indicate that although a legal framework for consumer protection is normatively available, its implementation has not been optimal. This is influenced by low consumer legal literacy, weak supervision and law enforcement, unclear responsibilities between business actors and marketplace platforms, and the suboptimal personal data protection system. Therefore, there is a need to strengthen regulations that are adaptive to digital transactions, enhance the role of marketplace platforms, and develop effective online dispute resolution mechanisms to ensure protection and legal certainty for consumers.